Deconstruction of female characters in short stories “al-mar'ah al-fātinah wa al-rajūl al-hakīm” - Mima, Rahmawan Wildani; Jafar, Jafar Shiddiq (Pusat Studi Gender dan Anak, 2024)
The world of women in literary works is still trapped in never-ending gender stereotypes. This qualitative library study aims to analyze and criticize the depiction of female characters in the short story Al-Mar'ah Al-Fātinah Wa Al-Rajūl Al-Hakīm deconstructively. In analyzing the short story, this study uses a feminist literary criticism perspective equipped with a deconstruction method. The results of this study are that Fatomi, as a female character in the story, is depicted as a woman who tends to be negative. It is different from the male character, who is portrayed positively. In addition, this study also indicates that with the data and facts the researcher found, women depicted negatively in a short story have a positive side implied in the short story. Among them is that women truly have a heroic, wise, and patient soul. As well as criticism of this short story as a conclusion to voice egalitarianism between men and women rationally and religiously.